Reinforcement of reclaimed sand by stimulating native microorganisms for biomineralization - Liu, Shiyu; Sui, Yujia; Dong, Bowen (Frontiers in Bioengineering and Biotechnology, 2022)
A response surface methodology was used to optimize a biostimulation solution to reinforce reclaimed sand by native microorganism-induced mineralization. First, the response surface methodology was used to obtain the optimal stimulation solution. Then, the effect of the optimal stimulation solution in inducing mineralization to reinforce reclaimed sand was evaluated. Finally, the reinforcement mechanism was revealed by SEM, XRD and microbial diversity analysis. The results showed that the urease activity of sample optimized by the response surface methodology was 1.17 times higher than that of the sample treated with the initial stimulation solution. The uniaxial compressive strength of samples treated with the optimal biostimulation solution and 1.0 M cementation solution over 15 cycles reached 3.94 MPa. The product of microbial mineralization was calcite, which was the main substance responsible for the improvement in the mechanical properties of the reclaimed sand. The concentration of the cementation solution not only affected the production of calcium carbonate but also affected the morphology of calcium carbonate crystals. After sample treatment with the stimulation solution, ureolytic microorganisms became the dominant bacteria in the sample. A comprehensive assessment of the reinforcement effect and cost revealed that using the optimal stimulation solution and 1.0 M cementation solution over 10 cycles was ideal for reinforcing reclaimed sand.